2010
DOI: 10.4314/ijbcs.v4i1.54247
|View full text |Cite
|
Sign up to set email alerts
|

Effets d’une couverture d’<i>Azolla</i> sur les performances de croissance et de production de <i>Clarias gariepinus</i> (Burchell) élevé en étangs

Abstract: RESUMEPendant 90 jours, nous avons mesuré le rôle de la couverture d'Azolla et la contribution relative de la nourriture endogène des étangs à la croissance et la production piscicole du poisson-chat africain Clarias gariepinus. Les poissons (poids moyen initial : 3,8 g) ont été soumis à trois modes d'élevage en étangs: (i) alimentation artificielle complémentaire seule (AL), (ii) Azolla seul en couverture de 40% de la superficie des étangs (AZ) et (iii) Azolla en couverture de 40% de la surface et nutrition c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…However, fisheries wastes recycling for fish farming is an economical and viable option for reducing environmental problems and simultaneously increasing animal protein production [35,[59][60][61]. The results of this study indicated that it is possible to totally replace FM with MFV in African catfish diet without affecting growth performance, thus confirming previous studies findings that animal by-product meals are acceptable protein sources for replacement of fishmeal in catfish diet [2,6,11,19,29,34]. Previous studies have reported beneficial effects [34,[62][63][64] but also adversely effects [65][66][67][68][69] of using MFV as protein sources in diets for several species.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, fisheries wastes recycling for fish farming is an economical and viable option for reducing environmental problems and simultaneously increasing animal protein production [35,[59][60][61]. The results of this study indicated that it is possible to totally replace FM with MFV in African catfish diet without affecting growth performance, thus confirming previous studies findings that animal by-product meals are acceptable protein sources for replacement of fishmeal in catfish diet [2,6,11,19,29,34]. Previous studies have reported beneficial effects [34,[62][63][64] but also adversely effects [65][66][67][68][69] of using MFV as protein sources in diets for several species.…”
Section: Discussionsupporting
confidence: 85%
“…The economically feasible catfish farming can be achieved when it is based on costeffective feed compound of locally available agricultural by-products [17,22,23]. Many alternatives resources such as feather meal [19], meat and bone meal, hydrolyzed feather meal, fleshings-meal and blood meal [24,25], dried fermented fish by-product silage [6], poultry silage [26], shrimp head waste meal [27,28], poultry by-product meal [2,29], skate meal and sablefish viscera meal [30] have been tried to replace fish meal either partially or fully, but even these meals of various animal sources are not sufficient to meet the growing demands of fish raising industry.…”
Section: Introductionmentioning
confidence: 99%
“…Azolla filiculoides is an aquatic fern, rich in proteins (Alalade and Iyayi, 2006) with a good profile in amino acids (Accodji et al, 2009;Leterme et al, 2009) and increasingly being utilised in developing fish feed (Abou et al, 2007;Abou et al, 2010). Likewise, earthworms are animal protein sources with high nutritive values (Sogbesan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Selon Sahli (2002) un pH compris entre 6 et 9 permet un développement de la faune et de la flore aquatique. Ces valeurs de pH obtenues dans les échantillons d'eau du lac Azili sont bonnes pour l'aquaculture car selon Abou et al (2010), elles se situent dans la limite tolérable des espèces de poissons qui est située entre 6,5 et 9. Quant aux valeurs de la turbidité observées au niveau des différents sites, ces valeurs sont supérieures à 5 NTU (norme OMS).…”
Section: -Discussionunclassified